2018
DOI: 10.33805/2638-8073.104
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Workplace Deviance Behaviors on Turnover Intention of Employees in Pakistan

Abstract: Workplace deviance behaviors are a negative fact that damages people who working within them and organizations without sound. This particular study is on finding out the Impact of Workplace Deviance Behaviors on Turnover Intentions of Employees in Pakistan. For this purpose researcher conduct a one short study that examine a sample of 110 employees from private and governmental organizations from Lahore, Pakistan. Our research help to people who want to know about Workplace Deviance and its consequences, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…For example, many researchers offer different names to the deviant behavior such as "dysfunctional behavior", "organizational misbehavior", "counterproductive work behavior", "non-complaint behavior" and among others. Specifically, research indicate workplace deviance behavior is linked with a huge variation of negative consequences, like lower level of confidence, decreased organizational commitment, increased absenteeism, increased on-the-job drug use/abuse, and actual turnover or turnover intention, among others (Mehar et al, 2018;Sang, Xuan, Ismail, Siti, & Tan, 2014).…”
Section: Workplace Deviant Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many researchers offer different names to the deviant behavior such as "dysfunctional behavior", "organizational misbehavior", "counterproductive work behavior", "non-complaint behavior" and among others. Specifically, research indicate workplace deviance behavior is linked with a huge variation of negative consequences, like lower level of confidence, decreased organizational commitment, increased absenteeism, increased on-the-job drug use/abuse, and actual turnover or turnover intention, among others (Mehar et al, 2018;Sang, Xuan, Ismail, Siti, & Tan, 2014).…”
Section: Workplace Deviant Behaviormentioning
confidence: 99%
“…A recent study of the Conference Board of Canada also estimated that due to absence from workplace Canadian economy have lost $16.6 billion In 2012, which is one of the forms of deviant behavior at work (Harisur, Howladar, Rahman, & Uddin, 2018). Employee deviance have negatively relationship with both customer satisfaction and corporate profitability (Mehar, Asif, & Hassan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the first line of the study explored the impact of WD and noted that less productivity and ineffective performance (Dunlop & Lee 2004), selection evaluation (Whiting & Maynes 2015), and turnover intention (Mehar et al 2018) are among the more egregious negative impacts of workplace deviance. The second line of study investigates the antecedents of workplace deviance and found that psychographic (Pletzer et al 2020), demographic, behavioural (Mackey et al 2021) situational factors (Guay et al 2016) and organizational factors, namely organizational commitment are responsible for such deviance.…”
Section: Abstrakmentioning
confidence: 99%